RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS) DAN DEBT TO EQUITY RATIO (DER) PENGARUHNYA TERHADAP CLOSING PRICE (CP) PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019 – 2021 - Drs.H.Friyanto,MSA,Ak,CA,CPA,CSRA,CSP,ACPA,CTA,CFRMP,CFRS.; Zuchruf Firdaus; Erwin Adi Prayogo (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2025)
This research was conducted with the aim of knowing and analyzing the influence of Return On Equity (ROE), Earning Per Share (EPS) and Debt to Equity Ratio (DER), on Closing Price (CP). In taking samples, this research used a purposive sampling method. The number of samples for this research was 14 companies with observations for 3 years so that the total research sample was 42 samples. The analysis used in this research is Multiple Linear Analysis, t Test (Partial), F Test (Simultaneous) and coefficient of determination test. The research results show that partially Return On Equity and Debt to Equity Ratio have no effect on Closing Price, while Earning Per Share partially has an effect on Closing Price. The research results simultaneously show that Return On Equity, Earning Per Share and Debt to Equity Ratio have an effect on Closing Price. The R² test (coefficient of determination) produces an R square value of 0.790 or 79%, this shows that the independent variable has a 79% influence on the Closing Price, while the remaining 21% is influenced by other variables outside this research.